The Palestinian issue and the Kurdish issue, similarity in essence and difference in positions = القضية الفلسطينية والقضية الكوردية، تشابه في الجوهر واختلاف في المواقف - Berghout, Abdelaziz; Suleiman, Luqman Abdullah (Al-Ameed Foundation for Development, Training and Development, 2024)
There is a historical and moral convergence between the Palestinian and Kurdish issues, and there are several similarities between the two causes. However, the Kurds feel that the Kurdish issue not only lacks the same support, attention, and solidarity that the Palestinian cause receives from official and popular institutions in the Islamic world, but their cause has also been subjected to much betrayal, distortion, and denial unjustly. This double standard by some Muslims, along with the contradiction and divergence in positions on similar Islamic issues, has sown hatred and animosity in the hearts of many Kurds, distancing them from focusing on the crucial issues of the Ummah and leading to much weakness and division in Arab-Kurdish relations. Therefore, the researcher believes that anyone who genuinely supports the Palestinian cause must stand by the Kurdish people's rights, including their right to self-determination, as mandated by general Islamic principles and high values of mutual recognition. Otherwise, they will be facing a contradiction filled with double standards. This is because the two issues are similar in essence, even though they differ in some details.